Impacto del marco institucional en el desarrollo de las organizaciones empresariales en el Perú - Díaz Andrade, Antonio (2002)
Exploratory research that seeks to identify aspects of the country's institutions that have influenced and influence, positively or negatively, the development of business organizations in Peru. The model designed shows the relations of interdependence between culture, education, State and globalization. The article also presents a conceptual framework to encourage serious debate on the importance of this issue and outlines guidelines on the role of business organizations in the economic and social development of the country.